A Luta Armada No Cinema. Ficcao, documentário, memoria - Trombetta, Jimena Cecilia (Imagofagia, 2021)
Sobre Seliprandy, Fernando. A Luta Armada No Cinema. Ficcao, documentário, memoria. São Paulo: Intermeios, 2015, 218 pp., ISBN: 978-85-8499-012-2.